Validitas Modul Pelatihan Self- Efficacy Sebagai Layanan Bimbingan Kelompok untuk Pencegahan Penyalahgunaan Narkoba - Maula, Anjany I'anatul; Nuryono, Wiryo (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2025)
Drug abuse in Indonesia is increasing, especially among teenagers, so effective prevention efforts are needed. One of the factors that plays a role in preventing drug abuse in self-efficacy, namely an individual’s belief in their ability to face difficult situations, including refusing drugs. This research aims to develop and validate a self-efficacy training module as an information service for preventing drug abuse for vocational school students. The research method used was expert validation using Gregory’s approach, involving six validators consisting of guidance and counseling experts and guide counseling teachers. The validation results show that the training module has a very high level of validity with a validity coefficient value of 1.00, makin it suitable for use as a learning medium. This module is expected to help guidance and counseling teachers in increasing students’ self-efficacy to reject drug abuse and support drug prevention programs in schools.